Genome-wide analysis of the laccase gene family in tossa jute (Corchorus olitorius): insights into stem development, lignification, and responses to abiotic stress - Deepak Kumar Jha; Deepak Kumar Jha; Subhadarshini Parida; Seema Pradhan; Nrisingha Dey; Shuvobrata Majumder (Frontiers in Plant Science)
Tossa jute (Corchorus olitorius) dominates global jute cultivation but has a high lignin content (13-14%) in its fibres, making them coarse and limiting their industrial applications. Reducing the lignin content requires a deeper understanding of the lignification process and the associated genes. Laccase (EC 1.10.3.2) is a key enzyme in the final step of lignin biosynthesis. A genome-wide analysis of the 361 Mb C. olitorius genome identified 46 laccase genes (ColLACs) from a total of 28,479 genes. In-silico analysis revealed that ColLAC genes are distributed across seven chromosomes, encode proteins ranging from 7.98 to 173.99 kDa, with 74 to 1548 amino acids and 10 conserved motifs. Additionally, 48.83% of ColLACs are predicted to be transmembrane proteins. Phylogenetic analysis classified them into eight groups, with GO term assignments suggesting their involvement in lignification. Tissue-specific expression analysis showed that 43.47% of ColLAC genes are predominantly expressed in roots, aligning with RNA-seq data. ColLAC gene expression varied across the developmental stages, from seedling to fibre harvest, and was influenced by heavy metal copper and abscisic acid (ABA) treatments. This variation correlated with upstream cis-acting elements. Ath-miR397 target sites were identified in 14 ColLAC genes, indicating potential post-transcriptional regulation. Further expression analysis in X-ray-induced bfs (bast fibre-shy) mutant tossa jute lines suggested that ColLAC34 is involved in both lignification and structural development, while ColLAC22, ColLAC40, and ColLAC46 play key roles in lignification. This study presents the first comprehensive genome-wide identification and characterization of the LAC gene family in jute. Understanding ColLAC functions could facilitate the development of low-lignin jute fibres, meeting the growing industrial demand for high-quality natural fibres of jute.